The Circular Economy and Organic Fraction of Municipal Solid Waste Recycling Strategies - Anna Rolewicz-Kalińska; Krystyna Lelicińska-Serafin; Piotr Manczarski (Energies, 2020)
Densely populated areas with large incoming populations have difficulty achieving high separate collection rates of municipal solid waste. The manuscript analyzes the link between biowaste collection and circular economy requirements as a fulfilment of the recycling rates and using biogas as a sustainable energy source. Three biowaste collection scenarios and three technical scenarios for its treatment are considered. The first scenario assumes only composting for biowaste treatment, the next includes also anaerobic digestion. In the years 2020–2050, the separate biowaste collection level will increase, depending on the scenario, from 26.9 kg/inh. up to 148.1kg/inh. By 2030, the quantity of biogas generated from biowaste can grow to almost 9 million m3/year, enabling the production of renewable energy at annual levels of almost 17 GWh and 69 TJ. Using the third scenario, the quantity of biogas generated grows more than twice (in 2035). If the capture rate of biowaste increases from 15% to 20% and then to 25%, the quantity of biogas generated grows by, respectively, 65% and more than 100%. Unfortunately, none of the scenarios enables the required municipal solid waste recycling rates in 2030 (60%) and 2035 (65%), which demonstrates the significant need to develop more effective separate collection systems, including biowaste. Methodology applied in the paper can be used for other cities and regions trying to meet circular economy demands.